The Economic Legacy of General Velasco: Long-Term Consequences of Interventionism - Martinelli, César (2019)
We apply synthetic control methods to study the long-term consequences of the interventionist and collectivist reforms implemented by the Peruvian military junta of 1968–1975. We compare long-term outcomes for the Peruvian economy following the radical reforms of the early 1970s with those of two controls made of similar countries, one chosen in the Latin American region and another one chosen from the world at large. We find that the economic legacy of the junta includes sizable loses in GDP along two decades, beyond those that can be attributed to adverse international circumstances. The evidence suggests that those loses can be attributed both to a decline in capital accumulation and to a fall in productivity.